Regulasi Perkawinan Dan Perceraian ASN Dalam Pergub Dki Jakarta No. 2 Tahun 2025: Studi Tentang Standar Moralitas - Moyang Raafi Wiguno; Muhammad Latif Fauzi (Family Law Study Program, Faculty of Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze Jakarta Governor Regulation No. 2 of 2025 concerning marriage and divorce permits for civil servants (ASN) as an instrument for shaping moral standards within the bureaucracy. This research employs an interdisciplinary qualitative approach, combining contemporary fiqh based on maqāṣid al-sharī‘ah and social analysis through netnography. Data were collected from legal documents, academic literature, and public discourse on digital platforms. The findings reveal that the regulation functions not merely as an administrative mechanism, but also as a state effort to construct moral standards in family life among civil servants, particularly through the protection of life, lineage, intellect, and property. Public discourse demonstrates diverse responses, ranging from support as a reinforcement of bureaucratic ethics to criticism viewing it as state intrusion into private life. This study contributes to the development of Islamic family law by demonstrating that state regulations can be understood as an actualization of maqāṣid al-sharī‘ah within modern public policy. It also highlights the importance of integrating legal, moral, and social dimensions in formulating responsive and equitable policies.